PENGARUH TEKNIK HIPNOTIS LIMA JARI DAN AROMA TERAPI MINT TERHADAP KECEMASAN PASIEN DENGAN GAGAL GINJAL KRONIK DI RUANG HEMODIALISA RSUD DR. HARYOTO LUMAJANG - Sri Wahyuni; Rizka Yunita; Titik Suhartini (NHM PRESS, 2023)
Chronic kidney failure is progressive kidney damage characterized by uremia (urea and other wastes circulating in the blood and its complications if dialysis or kidney transplantation is not performed). The research design used a pre-experiment with a one group pretest-posttest design approach. The population taken was patients with CRF undergoing hemodialysis at Dr. Haryoto Hospital Lumajang. The sampling technique used total sampling. The number of research samples was 60 research respondents according to the inclusion and exclusion criteria. Data collection was carried out using a questionnaire with the analysis of the Depondent's T test data. The results of the correlative test show that there is a significant effect between the administration of the Five Finger Hypnotic Technique and the Aromatherapy of Mint on Anxiety at Haryoto Lumajang General Hospital which is indicated by a p value of 0.015 <0.05 so that there is a significant relationship. The value of the respondent's anxiety before being given therapy was an average value of 21.2 after being given anxiety therapy the respondent experienced a decrease with an average value of 17.8. Anxiety is a condition where a person feels afraid because of the situation he will experience. Giving five finger hypnosis and aromatherapy can reduce anxiety due to the relaxing effect that is given. The results of this study can be used as a basis for anxious nursing care as well as for subsequent research regarding the anxiety of hemodialysis patients